Genetic anomaly and clinical history and its implication in paternity analysis. Issue 1 (2nd January 2018) - Serra, A.; Lopes, V.; Balsa, F.; Brito, P.; Corte-Real, F.; Bento, A.M.; Anjos, M.J.; Bogas, V.
Abstract : This paper describes a paternity case investigation that became a maternity investigation, in which the mother of two dizygotic male twins referred having received a bone marrow transplant, donated by her sister, seven years before, due to a sickle cell disease. The study of 17 STRs with different commercial kits revealed two maternal inconsistencies with one child and one inconsistency with the other. The alleged father was excluded as the biological father without genetic information of the mother. After receiving our report, the court decided to investigate the maternity relative to the children. Supplementary studies with more STRs and with other mother biological tissues revealed distinct genetic profiles in blood, epithelial cells and hair roots. The profile obtained from the hair roots was consistent with being the mother of her children. This case shows the importance of accurate information about the medical condition of all the involved persons, along with the collection of hair roots, especially when one of the participants has had a bone marrow transplant.